Reinventing the wheel: excitation of flow instabilities for active flow control using plasma actuators - Samimy, Mo; Webb, Nathan; Esfahani, Ata (Journal of physics. D, Applied physics, 2019)
Flow control is typically used to manipulate a flow's natural behavior to alter its effects on a vehicle or system. When active flow control (AFC) is used in aerospace applications, the actuation can be turned on/off or adapted to changing flight conditions. AFC techniques in which significant gains can be achieved with relatively small cost are most beneficial and are the subject of this paper. Flows with the Kelvin-Helmholtz (K-H) instability, which are present in many aerospace applications, are amenable to AFC and have been the subject of research for over five decades. The K-H instability can amplify any natural or artificially-seeded thermal, acoustic, or hydrodynamic perturbations over a wide range of frequencies. These perturbations can grow and eventually roll up into large-scale flow structures, which, in turn, can dominate important processes such as entrainment, mixing, momentum and heat trasport, and aeroacoustic noise. However, the application of active flow control was limited to low-speed flows in the earlier decades of study due to the shortcomings of the available actuators. The recent development of plasma actuators, capable of producing simultaneously high-amplitude and high-bandwidth thermal perturbations, has extended the AFC applications to high-speed and high-Reynolds number flows of interest in aerospace, hence the title: reinventing the wheel. In this paper, two classes of such plasma actuators, namely localized arc filament plasma actuators and nanosecond dielectric-barrier discharge plasma actuators, are briefly discussed and their applications in two very different flows are presented to highlight the advances made in the community in the use of plasma actuators for aerospace applications. In addition, there is a discussion of further advances that must be made in the development of these actuators to move the techniques from laboratory to in-flight use.